Problematika Pendidikan Indonesia di Era Globalisasi - Amir, Firman (Peneliti.net, 2024)
Education is the most important means for humanizing humans to become completely independent human beings, education in the broadest sense is formal education (elementary school, middle school, high school, up to college), non-formal (education in the community), and informal education (education in the family environment) . All of this is a process carried out by humans in order to socialize and adapt to the culture they follow. Education is a form of effort to maintain the existence of human life and culture. In other words, education is one of human culture's strategies to maintain the existence of human life itself. Viewed from an epistemological perspective, humans are intellectual creatures who can use their minds freely to seek the truth in their knowledge (truth). And from an ethical perspective, humans are creatures who have a conscience that allows them to behave and act in accordance with the truth they adhere to, their decisions and actions. If we analyze it together, it turns out that the problem of education in Indonesia is not only a matter of curriculum structuring, teacher professionalism, output of educational institutions, educational paradigms, and internal problems in the administration of other educational institutions. But more than that, there are external factors that also have a big influence on Indonesian education, namely poor people who cannot afford to go to school, disorientation of government policies, market-oriented education, and the vortex of globalization that we are currently facing.